O024 Modifying light environments according to individual circadian light sensitivity. (9th November 2022) - Stone, J; Cain, S; Phillips, A
Abstract: Introduction: Large inter-individual differences exist in how sensitive the circadian system is to light. Circadian light sensitivity can be affected by medications, such as antidepressants, and varies as a function of age and some mood disorders. Using a computational model, we investigated how differences in an individual's light sensitivity can be offset by changes in their light environment to maintain stable circadian timing. Methods: A previously validated computational model was used to simulate sleep and circadian timing under realistic assumptions about light and sleep schedules in day workers across two weeks. The model predicted circadian phase (dim light melatonin onset) and sleep onset/offset times for each day. Simulations were repeated varying two parameters: (i) light sensitivity, representing changes in the dose-response curve to light, and (ii) evening illuminance, representing home lighting levels after sunset. Results: Higher light sensitivity and higher evening illuminance levels resulted in systematically later predicted sleep and circadian timing. The effects of increasing light sensitivity could be offset by reducing the level of evening illuminance, with this relationship holding over a wide range of light sensitivity values. Low light sensitivity combined with high evening illuminance produced a non-entrained (non-24) phenotype; decreasing evening illuminance from this state resulted in stable entrainment. Discussion: We are only beginning to understand the influence of medications and health conditions on circadian light sensitivity. Our results show how modifications to evening light levels can be used to offset impacts of variable light sensitivity on sleep and circadian timing.